Controle térmico de mosca-das-frutas (Ceratitis capitata) (Wied.) em frutos da cajazeira (Spondias mombin L.) - Brito, Carlos Henrique de (2007)
The fruits flies cause large damages for world fruticulture, much for the damages direct of the infestation in the fruits, how much for the indirect damages with fruits exportation prohibition. Considering crescent demand of importation countries and Brazil potentialities for attempt, it was has been required establishment of favorable conditions for exportation sector development, as well higher exigency of quality for product by consumer. Quarantine treatment for fruits disinfestations includes priority physical methods, applicable by simple form or in combination. Among those, are important vapour and hot water, because showed many vantages on chemical control, but important obstacle to heat treatment for postharvest fruits control against insects infestation in fruits susceptibility at temperature and time required for effective treatment, no affecting physiology and fruits quality. Treatments based on heat use, constituted alternatives applicable on tropical fruits by possibility disinfestations and simultaneous control of insects and pathogens.